The Application of Character Education in Islamic Religion Education Learning in Smp Manarul Quran Paciran, Lamongan - ika puspitasari (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
Abstract: The purpose of this study was to find out how the application of character education through the teaching strategy of the teacher of Islamic education at SMP Manarul Quran Paciran Lamongan, and what factors support and inhibit the implementation of character education through teaching strategies of the teacher of Islamic education at SMP Manarul Quran Paciran Lamongan. This research method can be described: This type of research is qualitative, the object of research is the principal, vice principal, several teachers of Islamic education, and of course students; Data collection methods: observation, interview, and documentation, were analyzing the data using qualitative descriptive. The findings of this study can be concluded: First: The process of learning Islamic education at SMP Manarul Quran Paciran Lamongan runs in accordance with existing procedures, meaning that teachers can apply character education using existing methods and facilities. The strategy is realized through contextual learning with class-based assessments accompanied by remedial and enrichment programs. Strategy for implementing character education at SMP Manarul Quran Paciran Lamongan through learning activities, school culture development and learning activities center; Second: a) The inhibiting factors include: limited time available, use of methods that are acceptable to students, lack of part of student interest, lack of balance between school environment, and lack of creativity of some teachers in the use of learning methods; b) Supporting factors include: the teacher uses methods that can be accepted by students, the facilities and infrastructure that support learning, the holding of guidance for all teachers with the aim that teachers can apply learning tools. Keywords: Character education, learning process, application